Pengaruh ROA,ROE dan NPM Terhadap Pertumbuhan Laba Pada Perusahaan Rokok Yang Terdaftar Pada IDX - Meida, Anna; Humaira, Chairina; Agustina, Anita (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2023)
This study aims to analyze the effect of company financial performance on profit growth in cigarette companies listed on the IDX. The data for this research uses secondary data published on the Indonesian stock exchange and the website of each cigarette company in the form of financial reports for the 2017-2019 period. The financial statements are analyzed using profitability ratios. the ratios used are ROA, ROE, and NPM as independent variables. The results of this study are (H1) Return On Assets (ROA) has a negative and not significant effect on profit growth, (H2 ) Return On Equity (ROE) has a negative and not significant effect on profit growth, (H3) Net Profit Margin (NPM) positive and significant effect on profit growth.